Numerical methods in geotechnical engineering : proceedings of the Sixth European Conference in Geotechnical Engineering, Graz, Austria, September 2006 /: proceedings of the Sixth European Conference in Geotechnical Engineering, Graz, Austria, September 2006. (2006) - Unknown
No abstract available